When should Surgery be used for Recurrent Ovarian Carcinoma?. Issue 8 (August 2018) - Bommert, M.; Harter, P.; Heitz, F.; du Bois, A.
Abstract: Cytoreductive surgery is an important column in the treatment of primary ovarian cancer. Surgical outcome is one of the most important prognostic factors and one of the few prognostic variables that can be influenced by therapists. Retrospective studies suggested that only complete cytoreduction was associated with a benefit. Therefore, definition of predictors of complete resection is of the utmost importance to avoid surgical burden in patients with both limited benefit of the procedure and limited overall life expectancy. Two prospective multicentre randomised surgical trials in platinum-sensitive recurrent ovarian cancer (DESKTOP III [NCT #01166737] and GOG 213 [NSC #704865]) comparing secondary cytoreductive surgery followed by platinum-based chemotherapy versus chemotherapy alone have been conducted. The results of the DESKTOP III were recently presented at the American Society of Clinical Oncology meeting in Chicago. It showed a benefit of secondary cytoreductive surgery exclusively in patients with complete resection with a progression-free survival of 5.6 months ( P  < 0.001). This overview aims to support this task and concentrates on the currently available data regarding surgery in recurrent ovarian cancer.